2021
DOI: 10.1038/s41380-021-01330-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of brain white matter microstructure with cognitive performance in major depressive disorder and healthy controls: a diffusion-tensor imaging study

Abstract: Cognitive deficits are central attendant symptoms of major depressive disorder (MDD) with a crucial impact in patients’ everyday life. Thus, it is of particular clinical importance to understand their pathophysiology. The aim of this study was to investigate a possible relationship between brain structure and cognitive performance in MDD patients in a well-characterized sample. N = 1007 participants (NMDD = 482, healthy controls (HC): NHC = 525) were selected from the FOR2107 cohort for this diffusion-tensor i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…As a crucial connecting pathway between brain hemispheres, the CC plays a central role in interhemispheric integration. Meta-analyses [ 75 78 ] have shown reduced WM integrity in the CC across MDD, BD, and SZ, suggesting disruptions in WM interhemispheric connectivity as a common pathophysiological pathway in major mental disorders, being related to deficits in various emotional and cognitive processes, such as executive functions, attention, working and visual memory [ 75 , 77 , 79 81 ]. Specifically, alterations in the forceps minor of the CC, composed of fibers extending laterally from the genu of the CC and connecting the cerebral hemispheres anteriorly, primarily indicate impaired interhemispheric communication within the prefrontal cortex, whose involvement in BD has been elaborated in several studies e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As a crucial connecting pathway between brain hemispheres, the CC plays a central role in interhemispheric integration. Meta-analyses [ 75 78 ] have shown reduced WM integrity in the CC across MDD, BD, and SZ, suggesting disruptions in WM interhemispheric connectivity as a common pathophysiological pathway in major mental disorders, being related to deficits in various emotional and cognitive processes, such as executive functions, attention, working and visual memory [ 75 , 77 , 79 81 ]. Specifically, alterations in the forceps minor of the CC, composed of fibers extending laterally from the genu of the CC and connecting the cerebral hemispheres anteriorly, primarily indicate impaired interhemispheric communication within the prefrontal cortex, whose involvement in BD has been elaborated in several studies e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Further supporting a mechanistic role, meta-analyses have shown that late-onset depression show significantly greater WMH burden in late-onset LLD than in early-onset LLD [ 152 , 153 ]. The extent of ischemic injury extends beyond visible WMHs, as vascular risk factors compromise microstructural integrity in normal-appearing white matter [ 154 , 155 ]. Location of WMHs and microstructural changes may be critical, as LLD is associated with damage to the cingulum bundle, uncinate fasciculus, and superior longitudinal fasciculus [ 156 159 ].…”
Section: Factors Contributing To Depression Vulnerabilitymentioning
confidence: 99%
“…One explanation for these differences between patient and healthy control studies is that pharmacologically-induced improvements in cognition may only be seen in those with cognition-related pathophysiological abnormalities, such as progressive neurotoxicity and reduced neurogenesis [126,211]. For example, reduced grey and white matter integrity in frontal-limbic networks are both associated with cognitive impairment in MDD [212][213][214][215] and reduced neurotrophin and proinflammatory cytokine activity in MDD [216][217][218][219]. Indeed, baseline BDNF, including mature BDNF, and pro-inflammatory cytokine levels in individuals with MDD predicts cognitive improvement and antidepressant effects across a range of agents, including sertraline and vortioxetine [220][221][222][223], although it is important to note that peripheral measures of BDNF may not reflect central BDNF concentration [224].…”
Section: Inconsistency Of Cognitive Effects Across Clinical and Noncl...mentioning
confidence: 99%